Performance of a HER2 testing algorithm specific for p53‐abnormal endometrial cancer. Issue 4 (5th July 2021) - Vermij, Lisa; Singh, Naveena; Leon‐Castillo, Alicia; Horeweg, Nanda; Oosting, Jan; Carlson, Joseph; Smit, Vincent; Gilks, Blake; Bosse, Tjalling
Abstract : Aims: Human epidermal growth factor receptor 2 (HER2) amplification in endometrial cancer (EC) is almost completely confined to the p53‐abnormal (p53abn) molecular subtype and independent of histological subtype. HER2 testing should therefore be molecular subtype‐directed. However, the most optimal approach for HER2 testing in EC has not been fully established. Therefore, we developed an EC‐specific HER2 immunohistochemistry (IHC) scoring method and evaluated its reproducibility and performance to establish an optimal diagnostic HER2 testing algorithm for p53abn EC. Methods and results: HER2 IHC slides of 78 p53abn EC were scored by six gynaecopathologists according to predefined EC‐specific IHC scoring criteria. Interobserver agreement was calculated using Fleiss' kappa and the first‐order agreement coefficient (AC1). The consensus IHC score was compared with HER2 dual in‐situ hybridisation (DISH) results. Sensitivity and specificity were calculated. A substantial interobserver agreement was found using three‐ or two‐tiered scoring [κ = 0.675, 95% confidence interval (CI) = 0.633–0.717; AC1 = 0.723, 95% CI = 0.643–0.804 and κ = 0.771, 95% CI = 0.714–0.828; AC1 = 0.774, 95% CI = 0.684–0.865, respectively]. Sensitivity and specificity for the identification of HER2‐positive EC was 100 and 97%, respectively, using a HER2 testing algorithm that recommends DISH in all cases with moderate membranous staining in >10% of the tumour (IHC+). Performing DISH on all IHC‐2+ and ‐3+ cases yields a sensitivity and specificity of 100%. Conclusions: Our EC‐specific HER2 IHC scoring method is reproducible. A screening strategy based on IHC scoring on all cases with subsequent DISH testing on IHC‐2+/‐3+ cases has perfect test accuracy for identifying HER2‐positive EC. Abstract :